Οι θεωρίες περί εφηβικού εγωκεντρισμού: Μια κριτική παρουσίαση - Γαλανάκη, Ε. (Τετράδια Ψυχιατρικής, 1998)
In this article, we offer a brief description of the current theories of adolescent egocentrism, namely Piaget's, Elkind's and Lapsley's theories. Aspects from Blos', Mahler's and Josselson's psychodynamic views, as well as from Selman's theory of interpersonal understanding are integrated into Lapsley's theory. For each theory, the content, the source, the main forms and the developmental features of egocentrism are discussed. In conclusion, we attempt to evaluate the explanatory power of these theories and we suggest a model of adolescent egocentrism which includes physical, cognitive, social and emotional factors.